2022
DOI: 10.1186/s40643-022-00496-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of agro-waste-mediated silica nanoparticles to sustainable agriculture

Abstract: Use of green agronomic techniques for plant development and crop protection is essential for environmental sustainability. The current research investigates a more efficient and long-term technique of manufacturing silica nanoparticles (SiO2 NPs) from agricultural waste (sugarcane bagasse and corn cob). SiO2 NPs were synthesized by calcinations of waste residues in muffle furnace with varying temperatures (400–1000 °C)/2 h in the present of static air. Field emission scanning electron microscopy (FESEM), Fouri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The corresponding voltage and current were 40 kV and 30 mA, respectively. The average size of SiO 2 -NPs synthesized by fungal metabolites was calculated using the Debye–Scherrer Equation (1) [ 42 ]: D = (Kλ/β Cos θ) where D is the mean particle size, where K is the Scherrer constant, λ is wave length of the X-ray beam used (1.54, 184 Å), β is the Full width at half maximum (FWHM) of the peak and θ is the Bragg angle, respectively. The particle size distribution of the SiO 2 -NPs was evaluated using dynamic light scattering (DLS) measurements, which gives the hydrodynamic diameter of particles [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…The corresponding voltage and current were 40 kV and 30 mA, respectively. The average size of SiO 2 -NPs synthesized by fungal metabolites was calculated using the Debye–Scherrer Equation (1) [ 42 ]: D = (Kλ/β Cos θ) where D is the mean particle size, where K is the Scherrer constant, λ is wave length of the X-ray beam used (1.54, 184 Å), β is the Full width at half maximum (FWHM) of the peak and θ is the Bragg angle, respectively. The particle size distribution of the SiO 2 -NPs was evaluated using dynamic light scattering (DLS) measurements, which gives the hydrodynamic diameter of particles [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Silica from sugarcane bagasse is used for its antibacterial activities [237], photocatalysis ability against dyes [238,239] and heavy metals [152], used in agriculture [240], and has applications in hydrophobic coatings [241], insect control [242], membranes for wastewater purification [243,244], and fillers in polymeric composites [232]. Hikmah et al (2021) developed Fe 3+ -doped SiO 2 /TiO 2 composites using silica from sugarcane bagasse ash as an adsorption site to TiO 2 particles and promoted 98.18% degradation of Congo red dye through photocatalysis [238].…”
Section: Sugarcane-based Silicamentioning
confidence: 99%
“…Seed germination and growth were measured; silica improved plant biometrics and physiology. In addition, it served as an antifungal agent, with 73.42% inhibition of mycelia growth [240]. Saed et al (2021) tested the use of local diatomaceous earth with silica from sugarcane bagasse against insect pests.…”
Section: Sugarcane-based Silicamentioning
confidence: 99%
“…SiO 2 NPs are increasingly prepared from plants and agriculture byproducts. Researchers reported that SiO 2 NPs can effectively control Spodoptera littoralis, a polyphagous plant pest [11,15,27]. In a recent study of our lab (To be published), SiO 2 NPs prepared from amorphous silica powder derived from olive stones and corncobs were effectively impacted in larval mortality, pupal weight, larval and pupal development times of P. operculella.…”
Section: Introductionmentioning
confidence: 99%